Fenestration and dehiscence frequency in maxillary teeth with apical periodontitis: a CBCT study - Héctor Monardes; Karin Steinfort; Nuria Almonacid; Marcela Bustos; Jaime Abarca (Universidad de Antioquia, 2021)
Introduction: to determine the frequency of fenestration and dehiscence bone defects present in maxillary teeth with apical periodontitis, mainly in teeth with endodontic treatment, as they are frequently cause of nonspecific symptoms after treatment. Methods: 1201 Maxillary Cone Beam Computed Tomography (CBCT) exams were analyzed and 803 teeth with apical periodontitis were selected. Results: of the teeth with apical periodontitis, 142 had a fenestration defect (18%) of which 105 teeth (74%) were endodontically treated. The highest frequency was observed in premolars, with no statistical differences between groups. Dehiscence defect was found in 139 teeth (17%) out of which 90 (65%) were endodontically treated. The highest frequency was observed in molars, with statistical differences in relation to other tooth types (p< 0.001). Conclusion: an important number of teeth with apical periodontitis present dehiscence or fenestration bone defects, especially in teeth with root canal treatment.